Perbedaan pengetahuan menyikat gigi melalui penyuluhan dengan metode ceramah dan pemutaran video kartun pada murid sekolah dasar - Arnetty, Arnetty; Ifitri, Ika; Warman, Anses; Anggraini, Elsa Putri Ayu; Amiruddin, Amiruddin (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The reason why someone neglects dental and oral hygiene is a lack of knowledge. Knowledge is closely related to education. Dental and oral health education is a method to motivate individuals to clean their teeth and mouth effectively.Objectives: The aim of the research was to determine differences in toothbrushing knowledge through counseling using lecture methods and cartoon videos to students in grades IV and V at SDN 04 Air Pura, Pesisir Selatan Regency.Methods: The type of research used is a quasi-experimental type with a "pretest and posttest" design. The sampling technique used was a total population of 80 people. The way to collect data is by filling out a pretest and posttest questionnaire about good and correct tooth brushing. The data analysis used is univariate and bivariate analysis.Results: The results of the research showed that knowledge before being given counseling using the lecture method with good criteria was 32.5% then increased to 62.5%, while counseling using the method of playing cartoon videos with good criteria was 12.5% then increased to 55.0% after being given counseling using the method of playing cartoon videos.Conclusion: The conclusion of this research is that the lecture method and showing cartoon videos can both increase knowledge about good and correct tooth brushing. Keywords:Brushing teeth, Lecture Method, Cartoon Video